Isolated chondrosarcoma of frontal sinus (Bangladesh Journal of Otorhinolaryngology, 2012)
An uncommon case of chondrosarcoma involving frontal sinus is presented. Pertinent literature is reviewed to emphasize the management of this tumor at unusual site.DOI: http://dx.doi.org/10.3329/bjo.v18i1.10425  Bangladesh J Otorhinolaryngol 2012; 18(1): 81-83